TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENYEDIA SARANA PRAKTIK PROSTITUSI (TINJAUAN PUTUSAN NO.2156/PID.SUS/2016/PN-MDN) - Stefanus Marcius Stefanus Marcius; Theresia Simatupang (jurnal.unprimdn.ac.id, 2018)
In this social life, there are always social problems that continue to develop in line with times, especially the issue of prostitution. Prostitution is an issue that concern the dignity and value of women. The practice of prositution has attracted a lot of controversy, especially in Medan, the phenomenon of the prostitution is one the criminalization that is very difficult handled bye the government and local law, because this type of crime is supported by several factors, for example like economic problems, that stongly enonomic problems, that strongly encouraging someone to do the criminal practice. To address the phenomenon of prostitution in medan, it is not enough to be seen from one point view but must be comprehensive.